Advances in coincidence time resolution for PET. (25th February 2016) - Cates, Joshua W; Levin, Craig S
Abstract: Coincidence time resolution (CTR), an important parameter for time-of-flight (TOF) PET performance, is determined mainly by properties of the scintillation crystal and photodetector used. Stable production techniques for LGSO:Ce (Lu1.8 Gd0.2 SiO5 :Ce) with decay times varying from  ∼30–40 ns have been established over the past decade, and the decay time can be accurately controlled with varying cerium concentration (0.025–0.075 mol%). This material is promising for TOF-PET, as it has similar light output and equivalent stopping power for 511 keV annihilation photons compared to industry standard LSO:Ce and LYSO:Ce, and the decay time is improved by more than 30% with proper Ce concentration. This work investigates the achievable CTR with LGSO:Ce (0.025 mol%) when coupled to new silicon photomultipliers. Crystal element dimension is another important parameter for achieving fast timing. 20 mm length crystal elements achieve higher 511 keV photon detection efficiency, but also introduce higher scintillation photon transit time variance. 3 mm length crystals are not practical for PET, but have reduced scintillation transit time spread. The CTR between pairs of mm 3 and mm 3 LGSO:Ce crystals was measured to be and ps FWHM, respectively. Measurements of light yield and intrinsic decay time are also presented for a thorough investigation into the timing performance with LGSO:Ce (0.025 mol%).